Sosialisasi Peningkatan Kepuasan Pelanggan pada Kelompok Usaha Bareng Raya - Hajar, Granita; Fauzi, Muhammad Dzulfikar; Rakhmaddian, Nicko Nur; Matteo Ibastian (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2023)
After the Covid-19 pandemic hit for two years, UMKM began to move to improve themselves. The pandemic has made UMKM owners feel their turnover has dropped drastically. One way to increase sales turnover is by increasing customer satisfaction. Customer satisfaction is one of the essential things that UMKM must pay more attention to, by fulfilling customer desires it will increase customer satisfaction and UMKM will gain customer loyalty. Partners in community service this time are several UMKM in the Bareng Raya area, Malang. So that in this community service program, there will be an increase in customer satisfaction by providing knowledge and training on customer satisfaction criteria. Several methods can be used in measuring customer satisfaction, one of which is Service Quality (Servqual). We socialize with partners regarding appropriate criteria to increase customer satisfaction. Partners already understand the meaning of customer satisfaction and the criteria that are expected to be applied in developing their business.